Interplay between peer experiences and classroom behavioral engagement throughout early childhood: Intraindividual and interindividual differences. (August 2022) - Salvas, Marie-Claude; Archambault, Isabelle; Olivier, Elizabeth; Vitaro, Frank; Cantin, Stéphane; Guimond, Fanny-Alexandra; Robert-Mazaye, Christelle
Abstract: Developmental theorists emphasize the existence of reciprocal influences between children's peer experiences and their early classroom behavioral engagement. For school practitioners who must identify relevant intervention targets to design educational activities, estimating precisely how aspects of peer experiences and behavioral engagement jointly unfold over time is of key interest. In addition, it is important to differentiate between intraindividual and interindividual effects. Nevertheless, evidence of these reciprocal links or intra- and interindividual effects during the early stages of schooling is scarce. This study ( N  = 638 children) used a Latent Curve Model with Structured Residuals (LCM-SR) to disentangle interindividual differences (stable trait-like) from intraindividual changes (dynamic state-like) in the associations between peer experiences (social acceptance and friendship involvement) and children's classroom behavioral engagement from the beginning of kindergarten through Grade 2. Results indicated that the links between children's peer experiences and their behavioral engagement reflect their steady tendency to be well adjusted in the classroom as well as with peers, rather than highlighting reciprocal associations between these factors over time. However, results also underscored that children who showed high engagement tended to be concurrently more accepted by peers in the same school year in Grade 1 or Grade 2, beyond stable aspects of engagement and social acceptance. These findings support the need to develop educational practices to improve social acceptance as a way to foster behavioral engagement. They also indicate that behavioral engagement should be considered a concrete intervention target for school practitioners seeking to improve children's social acceptance during the school year.